Fetal fibronectin and microorganisms in vaginal fluid of women with complicated pregnancies - Anette Rossel Goffeng; Elisabet Holst; Ian Milsom; Göran Lindstedt; Per‐Arne Lundberg; BjöRn Andersch (Acta Obstetricia et Gynecologica Scandinavica)
Objectives. To determine vaginal fetal fibronectin in women with pregnancies complicated by preterm labor (PTL), preterm premature rupture of the membranes (PPROM) or bleeding; to investigate possible relationships to the vaginal microflora; and to assess the ability to predict preterm delivery from these measures. Material and methods. Group comparative study between women of the same gestational age with a normal pregnancy (n=28) and consecutive women admitted with PTL (n=63), PPROM (n=18) and bleeding (n=21). Samples of vaginal fluid were collected at the time of admission in complicated pregnancies and from the women with normal pregnancies. Fetal fibronectin was determined by enzyme immunoassay and quantitative aerobic and anaerobic microbiological cultures were performed. Results. The number of positive (± 0.05 mg/L) vaginal fetal fibronectin values was higher among women with PTL, PPROM and bleeding compared to controls (p<0.001). A positive fibronectin value was predictive of delivery ± 34 weeks (sensitivity 64%, specificity 87%). The absence of hydrogen peroxide‐producing lactobacilli was predictive for preterm delivery <34 weeks (sensitivity of 100%, specificity 35%). Conclusions. The presence of vaginal fibronectin and the absence of hydrogen peroxide‐producing lactobacilli was indicative of an increased risk for preterm delivery < 34 weeks.